Jazz Cosmopolitanism in Accra: Five Musical Years in Ghana. Steven Feld. 2012. Durham, NC: Duke University Press. 328 pp. - Schauert, Paul (International Library of African Music, 2012)
pages: 176-178
Keywords: Cosmopolitanism; Jazz; West Africa; African Music; Accra; Ghana; Transnational Culture